Health and wellbeing among retired elite athletes - Pena-Pérez, A.; Portela-Pino, I. (Journal of Human Sport & Exercise, 2023)
Objectives The implications that sport retirement generates among high-level athletes has led to an increase in scientific investigations which describe the quality of life associated to the athletes´ health. The main objective of the study was to determinate the primary problems faced by retired athletes.